Mapping pediatric brain tumors to their origins in the developing cerebellum - Okonechnikov, Konstantin; Joshi, Piyush; Sepp, Mari; Leiss, Kevin; Sarropoulos, Ioannis; Murat, Florent; Sill, Martin; Beck, Pengbo; Chan, Kenneth Chun-Ho; Korshunov, Andrey; Sahm, Felix; Deng, Maximilian; et al. (Neuro-Oncology, 2023)
Distinguishing the cellular origins of childhood brain tumors is key for understanding tumor initiation and identifying lineage-restricted, tumor-specific therapeutic targets. Previous strategies to map the cell-of-origin typically involved comparing human tumors to murine embryonal tissues, which is potentially limited due to species-specific differences. The aim of this study was to unravel the cellular origins of the 3 most common pediatric brain tumors, ependymoma, pilocytic astrocytoma, and medulloblastoma, using a developing human cerebellar atlas.We used a single-nucleus atlas of the normal developing human cerebellum consisting of 176 645 cells as a reference for an in-depth comparison to 4416 bulk and single-cell transcriptome tumor datasets, using gene set variation analysis, correlation, and single-cell matching techniques.We find that the astroglial cerebellar lineage is potentially the origin for posterior fossa ependymomas. We propose that infratentorial pilocytic astrocytomas originate from the oligodendrocyte lineage and MHC II genes are specifically enriched in these tumors. We confirm that SHH and Group 3/4 medulloblastomas originate from the granule cell and unipolar brush cell lineages. Radiation-induced gliomas stem from cerebellar glial lineages and demonstrate distinct origins from the primary medulloblastoma. We identify tumor genes that are expressed in the cerebellar lineage of origin, and genes that are tumor specific; both gene sets represent promising therapeutic targets for future study.Based on our results, individual cells within a tumor may resemble different cell types along a restricted developmental lineage. Therefore, we suggest that tumors can arise from multiple cellular states along the cerebellar “lineage of origin.”
Online veröffentlicht: 03. August 2023
Gesehen am 14.11.2023